Case report: Multiple epstein-barr virus-associated smooth muscle tumours in a child with IL-2-inducible T-cell kinase mutation of undetermined clinical significance - Wen, Qiongli; Ning, Jing; Mao, Zhiqun; Long, Xiangdang; He, Xiangling; Chen, Zhihong; Di, Qiuyi; Li, Qiaorong; Zhuo, Yu; Zhong, Gang (Frontiers in Pediatrics, 2023)
Abstract Background: EBV-associated smooth muscle tumours (EBV-SMTs) are uncommon neoplasms associated with immunodeficiency. The pathogenesis of EBV-SMTs is poorly understood. IL-2-inducible T-cell kinase (ITK), a member of the Tec family of tyrosine kinases, is the predominant Tec kinase in T cells. Researchers have shown that ITK is involved in the pathogenesis of autoimmune diseases and carcinogenesis, and the loss of ITK function due to mutation in patients can lead to EBV-associated lymphoproliferation. Multiple Epstein-Barr virus–associated smooth muscle tumours with ITK mutation have rarely been reported. Case presentation: A 6-year-old female child was admitted to the hospital due to recurrent bilateral hip pain for more than one year. Tumours were found in the lung, near the intracranial cavernous sinus and in the lumbar spine and paraspinal soft tissues by CT and MRI. The patient underwent vertebral tumour biopsy, which suggested low-grade myogenic or inflammatory myofibroblastic tumours, so the patient was given three courses of chemotherapy without symptom relief or mass reduction. The patient underwent lumbar mass resection, the pathological results indicated EBV-SMT, and a novel germline homozygous deletion mutation in the ITK gene was detected. The deletion mutation in this gene has not yet been reported and the clinical significance of the pathogenicity of the variant is unknown. Intrabronchial mass resection was performed under fibre bronchoscopy, and the pathological results indicated EBV-SMT. No significant recurrence or progression was observed after more than 2 years of follow-up. Conclusions: We present a rare case of multiple EBV-SMTs combined with ITK gene mutation. Some of the tumours were removed, and some were treated conservatively. There was no significant recurrence or progression after more than two years of follow-up. The optimal treatment regimen still needs to be further explored，and the relationship between ITK gene mutation at this locus and immunodeficiency and EBV-SMT warrants further investigation.